Understanding the maternal-infant nexus from dental histology and high-resolution compositional biogeochemistry: implications for bioarchaeological research - Alessia Nava (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The close maternal-infant relationship during pregnancy and early infancy is still an under-explored aspect of past human lives. Information about this nexus, which is driven by both biological and cultural characteristics, can be derived from the study of mineralised dental tissues, since teeth preserve a permanent record of an individual’s biological life history from intra-uterine life to the first years after birth and up to early adulthood. Furthermore, a record of the mother-infant dyad’s health status, diet and mobility during pregnancy is preserved in tissues that formed prenatally. State-of-the-art approaches to studying infants’ growth trajectories, physiological stresses and mother-infant health status include both classic and non-destructive virtual histomorphometry. Furthermore, because human growth and development, from the earliest phases of ontogenesis, correlate strongly with dietary patterns, laser-based biogeochemical analyses of dental enamel can also be used to reconstruct the maternal diet – including during pregnancy – nursing practices and mobility patterns at very high temporal resolution. Models for the incorporation of trace elements in dental enamel and their correlation with major dietary shifts have been derived from analyses of exfoliated deciduous teeth of contemporary infants whose biological life histories are well known. These models make up an interpretative toolkit to disentangle subtle variations in individual diets at sub-weekly resolution. This contribution presents an overview of state-of-the-art high-resolution compositional biogeochemistry coupled with dental histomorphometry as a tool to deepen our knowledge of the mother-infant nexus in archaeological and palaeoanthropological contexts, and to investigate, at the highest possible temporal resolution, women’s and children’s survival and adaptation strategies over the course of human evolution.